Development of a low-cost timer-based drip irrigation system for sustainable waxy corn cultivation in El Niño-prone regions - Hasbi, Muhammad; Darma, Rahim; Mohd Nawi, Nolila; Bakheet Ali, Hamed Noralla; Maulidyah, Nurul; Abdul Syakur, Kemal (Walter de Gruyter GmbH, 2026)
Water scarcity significantly threatens smallholder agriculture in Indonesia, Exacerbated by El Niño and climate change. Traditional irrigation practices often lead to water inefficiencies and yield losses, particularly in drought-prone regions. This study addresses these challenges by developing and evaluating a unique, low-cost, timer-based, semi-automatic drip irrigation system. This system, tailored for waxy corn farming in South Sulawesi, offers a practical and cost-effective solution for water scarcity. The objective was to enhance water-use efficiency, sustain crop productivity, and assess the economic feasibility of this system as a scalable solution for smallholders in the region. The field experiment, which adjusted irrigation scheduling based on plant growth stages and compared it to conventional practices, yielded promising results. The system achieved a water-use efficiency of 3.87 kg/m3, categorized as 'good to outstanding,' and delivered consistent yields while reducing manual labor and water wastage. The short payback period of 1.4 planting cycles makes it financially accessible for smallholder adoption, further highlighting the potential impact of the system. This system offers a practical alternative to high-tech sensor-based models, bridging the gap between advanced irrigation technologies and the needs of resource-constrained farmers in developing countries. This study recommends broader implementation supported by policy incentives, farmer training, and infrastructure investment. Future improvements could include the integration of real-time monitoring tools to optimize water delivery and expand adaptability across diverse agro-climatic conditions in the region. This adaptability ensures that smallholder farmers can confidently adopt the system in various regions of Indonesia.